Childhood violence exposure and externalizing behaviors: A systematic review of the role of physiological biomarkers. (November 2022) - Chong, Li Shen; Gordis, Elana; Hunter, Laura; Amoh, Jennifer; Strully, Kate; Appleton, Allison A.; Tracy, Melissa
Abstract: Childhood exposure to violence has been consistently linked to externalizing behaviors like delinquency and aggression. Growing evidence indicates that physiological biomarkers from the parasympathetic and sympathetic nervous systems (PNS and SNS) and hypothalamic-pituitary-adrenal (HPA) axis may moderate or mediate the relation between childhood violence exposure and externalizing behaviors. We conducted a systematic review to synthesize recent findings on physiological biomarkers as mediators and/or moderators of this association across the life course, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Our search yielded 3878 articles, of which 44 met inclusion criteria (describing a total of 46 independent studies). We found consistent evidence for blunted HPA-axis reactivity as a mediator of the relation between childhood violence exposure and subsequent externalizing behaviors, and for non-reciprocal PNS/SNS activation as moderators exacerbating this relation. However, the results of the majority of included studies that demonstrated significant moderating effects of physiological biomarkers varied by participant sex, type of childhood violence exposure, and type of stimuli used to induce physiological reactivity. The observed mixed findings are consistent with some theories that emphasize that both high and low stress reactivity can be adaptive depending on one's early environment. These findings highlight the need for systematic explorations of heterogeneity, theory-driven research questions, and longitudinal studies that span multiple developmental periods and multiple biological systems. Clinical implications include the need to assess physiological biomarkers in treatment and intervention studies and the potential to target interventions based on both autonomic functioning and environmental contexts. Highlights: Childhood violence exposure is an established predictor of externalizing behavior. Physiological biomarkers may moderate or mediate this relation. We found more evidence of physiological biomarkers as moderators than mediators. High and low reactivity, and non-reciprocal SNS/PNS activation, increased risk. Findings varied by type of biomarker, assessment methods, and participant sex.